2006
DOI: 10.1007/s00425-006-0374-1
|View full text |Cite
|
Sign up to set email alerts
|

APETALA2 like genes from Picea abies show functional similarities to their Arabidopsis homologues

Abstract: In angiosperm flower development the identity of the floral organs is determined by the A, B and C factors. Here we present the characterisation of three homologues of the A class gene APETALA2 (AP2) from the conifer Picea abies (Norway spruce), Picea abies APETALA2 LIKE1 (PaAP2L1), PaAP2L2 and PaAP2L3. Similar to AP2 these genes contain sequence motifs complementary to miRNA172 that has been shown to regulate AP2 in Arabidopsis. The genes display distinct expression patterns during plant development; in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 55 publications
3
27
0
Order By: Relevance
“…This was also shown previously for the regulation of glossy15, which encoded a two-AP2 domain protein from maize (Lauter et al, 2005;Nilsson et al, 2007). L1 forms from Norway spruce, pine and hybrid larch showed that this site was totally complementary and located at the 3 0 end of cDNA.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…This was also shown previously for the regulation of glossy15, which encoded a two-AP2 domain protein from maize (Lauter et al, 2005;Nilsson et al, 2007). L1 forms from Norway spruce, pine and hybrid larch showed that this site was totally complementary and located at the 3 0 end of cDNA.…”
Section: Resultssupporting
confidence: 64%
“…Two explanations could be proposed: (i) the sequence of L2 form in pine is divergent due to a change in the selective pressure acting on the gene or (ii) the sequence corresponds to a paralogous gene and the real ortholog of L2 form in pine has not yet been identified. A third form was recently described in P. abies (Nilsson et al, 2007). PaAP2L3 is undoubtedly the sister group of Gnetum parvifolium AP2, with a bootstrap proportion of 98%.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Relatively high degrees of homology were also indicated between this cDNA and the AP2-like sequences from Arabidopsis. Additionally, we showed strong complementarity between CeAP2-like mRNA and miR172, as well as localization of the complementary nucleotides similar to that in the cDNAs of other homologous genes identified in different plant species (Nilsson et al, 2007;Varkonyi-Gasic et al, 2012). These results indicated the potential regulation of AP2 by miR172 in the orchid.…”
Section: Disscussionsupporting
confidence: 48%
“…In fact, miR156 and miR172 are expressed in opposite temporal patterns, suggesting that the miR156 module may regulate the expression of miR172 (Willmann and Poethig, 2007). In addition, Nilsson et al (2007) suggested that the AP2 gene in spruce has the capacity to substitute an A class gene required in flower development. Additional studies are now required to determine the basis for this regulation and the complicated regulating network.…”
Section: The Diversity and Multiplicity Of Mirna Targets In Tomatomentioning
confidence: 96%